Three-dimensional nonreciprocal transmission in a layered nonlinear elastic wave metamaterial. (October 2020) - Li, Zhen-Ni; Wang, Yi-Ze; Wang, Yue-Sheng
Abstract: In this investigation, three-dimensional nonreciprocal transmission is realized by the combination of structural asymmetry and material nonlinearity. Analytical solutions of the coupled quasi-longitudinal (qP) and quasi-shear (qS1 and qS2 ) waves are derived. According to Bloch's law and the stiffness matrix method, we obtain the band gaps and the transmission coefficients of the fundamental and double frequency waves. We also discuss the effects of the incident azimuthal angle on the propagation behaviors in nonlinear phononic crystals and elastic wave metamaterials. This present work is expected to help design practical devices of nonreciprocal transmission with vector characteristics. Highlights: Three-dimensional nonreciprocal transmission is realized by material nonlinearities. Analytical solutions of coupled quasi-longitudinal and quasi-shear waves are derived. The effects of incident azimuthal angles on the propagation behaviors are discussed.